PERANCANGAN MANAJEMEN PROYEK SISTEM INFORMASI : SISTEM INFORMASI KONTRAKTOR - Habibie Pratama A. N.; Kelvin K. Saputra; Egy Patriasta; Luthfi Nurfarizi Ahmad; Krisman Jonatal Siregar; Agung Wijoyo (CV. Multi Kreasi Media, 2024)
Project activities and implementation consist of various processes and procedures that must be carried out jointly between contractors, consultants and stakeholders as capital holders. The implementation of data technology in this activity aims to help and facilitate the management of budget processes, innovations, changes and other policies that are strategic in nature. The design of a project management data system is expected to be a reference and a source of solutions for this case.